1999
DOI: 10.1182/blood.v93.9.3088
|View full text |Cite
|
Sign up to set email alerts
|

A New Fusion Gene TPM3-ALK in Anaplastic Large Cell Lymphoma Created by a (1;2)(q25;p23) Translocation

Abstract: Anaplastic large cell lymphomas (ALCL) are frequently associated with the t(2;5)(p23;q35). This translocation fuses the nucleophosmin (NPM) gene at 5q35, which encodes a nucleolar protein involved in shuttling ribonucleoproteins from the cytoplasm to the nucleus, to the anaplastic lymphoma kinase (ALK) gene at 2p23, encoding a tyrosine kinase receptor. In this report, we describe a typical case of ALCL whose malignant cells exhibited a novel (1;2)(q25;p23) translocation. These cells expressed ALK protein, but,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 257 publications
(70 citation statements)
references
References 41 publications
2
67
0
1
Order By: Relevance
“…The most frequent variant translocation is the t(1;2)(q25;p23), found in 15% to 18% of ALK+ ALCLs (Lamant et al , ). In theses cases, which express the TPM3‐ALK protein, ALK staining is restricted to the cytoplasm of malignant cells and in virtually all cases there is stronger staining on the cell membrane.…”
Section: Genetics and Molecular Findingsmentioning
confidence: 99%
“…The most frequent variant translocation is the t(1;2)(q25;p23), found in 15% to 18% of ALK+ ALCLs (Lamant et al , ). In theses cases, which express the TPM3‐ALK protein, ALK staining is restricted to the cytoplasm of malignant cells and in virtually all cases there is stronger staining on the cell membrane.…”
Section: Genetics and Molecular Findingsmentioning
confidence: 99%
“…Very recently, two fusion partner genes of NTRK1, TFG and TPM3, were reported to fuse to ALK in anaplastic large cell lymphoma (Lamant et al, 1999; Hernandez et al, 2002). It has been demonstrated that three different variants of TFG‐ALK involving different breakpoints in TFG gene, have in vitro transforming potential and bind to signal transduction pathway proteins such as Grb2, Shc, and PLCγ (Hernandez et al, 2002).…”
Section: Ret and Ntrk1 Oncogenes In Papillary Thyroid Cancermentioning
confidence: 99%
“…Different ALK translocations can also be seen in ALK + ALCL and presumably employ similar mechanisms. Other ALK fusion partners in paediatric ALCL include TPM3 at 1q25 (Lamant et al , ), TFG at 3q21 (Hernandez et al , ), ATIC due to cryptic inversions in chromosome 2 (p23q35) (Colleoni et al , ; Trinei et al , ), CLTC at 17q23 (Touriol et al , ; Cools et al , ), MSN at Xq11‐12 (Tort et al , ), TRAF1 at 9q32 (Abate et al , ) and MYH9 at 22q11·2 (Lamant et al , ). Also, ALK fusions are not unique to ALCL, as these translocations or others occur in neoplasms, such as DLBCL, inflammatory myofibroblastic tumour, colon and breast cancer, renal cell and esophageal squamous cell carcinoma, plasmacytoma and non‐small‐cell lung cancer (Boi et al , ).…”
Section: Anaplastic Large Cell Lymphomamentioning
confidence: 99%